The Relationship Between Workload, Job Satisfaction and Absenteeism Among Staff Nurses at Institut Jantung Negara (IJN) - Adiwayu Ansar, Zainuddin (2012)
The main purpose of this study is to examine and to better understand on the reasons that causes absenteeism among staff nurses in Institut Jantung Negara, Malaysia. This study was done on 171 registered nurses of IJN and data obtained from questionnaires and were being analyzed by using Statistical Package for Social Science (SPSS) version 16. The statistical method of Pearson Correlation was used to determine the existence of the relationship between the independent variables which are Job Satisfaction and Workload with the dependent variable : Absenteeism. Cronbach Alpha was used to further illustrate the reliability test. Throughout the statistical analysis of correlation analysis, it is found that there is a significant relationship between workload and absenteeism (r2 = -0.464 ; p ≤ 0.01). However for job satisfaction and absenteeism, it was found that there is no significant relationship between the variables (r2 = -.140 ; p ≥ 0.05). This study will assist and help Institut Jantung Negara to determine the main causes of absenteeism among staff nurses in IJN. It will also help to improve on its employee attendance as well further enhancing the absenteeism policy in the organisation